An Analytical Study of the Responses of Advanced Students of Translation to Different Translation Problems* - Suzan Mohammed Qasim _ Kadhim Al-Ali ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The present study aims to evaluate the students’ theoretical background knowledge about translation which they have developed throughout their academic study as well as exploring the most difficult translation problems for the students. The study consists of a set of important preliminaries. Review of related literature, methodology followed and finally the conclusions which are based on the results in addition to the recommendations and suggestions for further studies.